Meningococcal carriage among Hajj pilgrims, risk factors for carriage and records of vaccination: a study of pilgrims to Mecca. Issue 4 (31st January 2021) - Alasmari, Abrar; Houghton, Joanna; Greenwood, Brian; Heymann, David; Edwards, Phil; Larson, Heidi; Assiri, Abdullah; Ben‐Rached, Fathia; Pain, Arnab; Behrens, Ron; Bustinduy, Amaya
Abstract: Objective: The Saudi government requires that all pilgrims receive a quadrivalent meningococcal vaccine at least 10 days before the Hajj. We conducted a study to determine the uptake of meningococcal vaccine and antibiotic use. We also investigated risk factors of meningococcal carriage and carriage of Neisseria meningitidis pathogenic serogroups A, C, W and Y. Methods: A cross‐sectional oropharyngeal carriage survey was conducted in 2973 Hajj pilgrims in September 2017. A real‐time polymerase chain reaction (rt‐PCR) assay was used to identify N. meningitidis from the oropharyngeal swabs. A questionnaire investigated potential risk factors for carriage of N. meningitidis . Results: Two thousand two hundred forty nine oropharyngeal swabs were obtained. The overall prevalence of carriage of N. meningitidis was 4.6% (95% CI: 3.4%–6%). Carriage of pathogenic serogroups was not associated significantly with any of the meningococcal risk factors evaluated. 77% of pilgrims were vaccinated but 22.58 % said they were carrying unofficial vaccination cards. Conclusion: Carriage of serogroups A, C, W and Y was not significantly associated with any of the risk factors investigated. Almost a quarter of pilgrims were unlikely to have been vaccinated, highlighting a need to strengthen compliance with the current policy of vaccination to prevent meningococcal disease outbreaks during and after the Hajj.